Role of Chest Radiograph in Diagnosis of Acyanotic Congenital Heart Disease - Siregar, Muhammad Harmen Reza; Daulay, Elvita Rahmi; Hasan, Refli (Journal of Society Medicine, 2022)
Background: Early diagnosis of acyanotic congenital heart disease could lead to early referral and treatment before the onset of irreversible sequelae. Despite the development of modern imaging methods, conventional chest radiographs remain an important component of diagnostic process in pediatric cardiology. The aim of this study is to determine the accuracy of the results of chest X-ray examination with echocardiography results in patients with suspected acyanotic congenital heart disease at H. Adam Malik General Hospital Medan in 2019-2020. Methods: This study was a retrospective cross-sectional analytical observational study with a diagnostic test design to compare the sensitivity and specificity of conventional chest radiography compared with echocardiography of patients with suspected acyanotic CHD with shunts. The sample population was all children <18 years with suspicion of cyanotic CHD who came for treatment at H. Adam Malik Hospital Medan in the period January 2019 - December 2020. The study used data from medical records at H. Adam Malik Hospital Medan. The collected data is then analysed for diagnostic tests. Results: This study had a sample of 64 people with the highest proportion of samples being women, the average age was 67.9±54.1 months, and the results of echocardiography of the ductus arteriosus were persistent. The results of the diagnostic test showed a sensitivity of 78% and specificity of 80%, 95% PPV value and 40% NPV value, LR+ 3.8 and LR- 0.2. Conclusions: chest X-ray is adequate as a diagnostic tool in acyanotic congenital heart disease with left-to-right shunt. Clinical suspicion accompanied by chest X-ray results suggesting acyanotic congenital heart disease should be further assessed.